Gender-Based Disparities in Adolescent Overweight: Findings from the Thailand Global School-Based Student Health Survey (GSHS): IN PRESS - Purwo Setiyo Nugroho; Kusuma Estu Werdani (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Adolescent overweight is an increasing public health concern in Thailand, driven by rapid lifestyle changes and urbanization. However, gender differences in factors associated with overweight remain insufficiently understood. This study conducted a secondary analysis of data from the 2021 Global School-Based Student Health Survey (GSHS), a nationally representative survey using a stratified two-stage cluster sampling design. A total of 4,510 adolescents aged 13–17 years were included. Data were analyzed using univariate, bivariate, and multivariate logistic regression, and sex stratified analyses were performed to identify factors associated with overweight. Overweight prevalence was highest among boys aged 13 years and girls aged 15–16 years. Among boys, overweight was significantly associated with younger age, food insecurity, and psychosocial distress. Among girls, dietary behaviors, sedentary lifestyle, and parental support showed stronger associations. Insufficient parental monitoring increased the likelihood of overweight in both sexes. Smoking was inversely associated with overweight among boys (OR=0.697, 95% CI: 0.691–0.704) but positively associated among girls (OR=1.236, 95% CI: 1.225–1.247). Overweight girls also reported higher levels of psychosocial problems, including bullying, loneliness, suicidal ideation, and sleep disturbances. Adolescent overweight in Thailand is influenced by multiple determinants that differ by gender. Gender sensitive interventions are needed, focusing on psychosocial well being and food security for boys, and healthy eating, parental involvement, and reduced sedentary behavior for girls to address the growing burden of adolescent overweight.